Epirubicin, Cisplatin, and Capecitabine for Primary Platinum-Resistant or Platinum-Refractory Epithelial Ovarian Cancer: Results of a Retrospective, Single-Institution Study. Issue 6 (1st July 2015) - Sayal, Karen; Gounaris, Ioannis; Basu, Bristi; Freeman, Sue; Moyle, Penny; Hosking, Karen; Iddawela, Mahesh; Jimenez-Linan, Mercedes; Abraham, Jean; Brenton, James; Hatcher, Helen; Earl, Helena; et al.
Abstract : Objective: Primary platinum-resistant epithelial ovarian cancer (EOC) is an area of unmet medical need. There is limited evidence from small studies that platinum-based combinations can overcome "resistance" in a proportion of patients. We investigated the efficacy and toxicity of platinum-based combination chemotherapy in the platinum-resistant and platinum-refractory setting. Methods: Epirubicin, cisplatin, and capecitabine (ECX) combination chemotherapy was used at our institution for the treatment of relapsed EOC. From the institutional database, we identified all patients with primary platinum-refractory or platinum-resistant relapse treated with ECX as second-line therapy between 2001 and 2012. We extracted demographic, clinical, treatment, and toxicity data and outcomes. We used logistic and Cox regression models to identify predictors of response and survival respectively. Results: Thirty-four 34 patients (8 refractory, 26 resistant) were treated with ECX. Response Evaluation Criteria In Solid Tumors (RECIST) response rate was 45%, median progression-free survival (PFS) was 6.4 months, and overall survival (OS) was 10.6 months. Platinum-resistant patients had better outcomes than did platinum-refractory patients (response rate, 54% vs 0%, P = 0.047; PFS 7.2 vs 1.8 months, P < 0.0001; OS 14.4 vs 3 months, P < 0.001). In regression models, time to progression after first-line treatment and platinum-refractory status were the strongest predictors of response and PFS or OS, respectively. Patients with time to progression after first-line treatment longer than 3 months showed PFS and OS of 7.9 and 14.7 months, respectively. Toxicity was manageable, with only 13% of cycles administered at reduced doses. Conclusions: Epirubicin, cisplatin, and capecitabine seems to be active in platinum-resistant relapsed EOC with manageable toxicity. Further prospective investigation of platinum-anthracycline combinations is warranted in patients who relapse 3 to 6 months after first-line platinum-taxane treatment.